Learner-Centred Teaching Contributes in Promising Results in Improving Learner Understanding and Motivation: A Case Study at Malaysia Tertiary Education - Yap, W. L.; Neo, Mai; Neo, Tse Kian (Academic Conferences and Publishing International Limited, 2016)
In Malaysia, traditional teaching is still a common approach among many lecturers. There have been many studies reported its limitations and many lecturers have started to adopt more learner-centred teaching approach to promote better learner understanding and learner motivation. Throughout this effort, it is noticed there are lecturers who could not be assured and felt uncertain about this transition because they went through traditional teaching environment during their studies. Due to this, the effort in shifting from traditional teaching to a more learner-centred teaching has been challenging and hard-hitting. Nevertheless, educational and multimedia technology has played an important role in creating a more interesting and engaging learning environments for our digital natives in this 21st century. In this research, a framework is to be proposed based on Weimer’s Learner-Centred Teaching model and through the incorporation of educational technology and multimedia technology in the learning environments. This proposed framework describes how this learner-centred teaching environment could promote better learner experiences by increasing retention rate and improving learner motivation. This proposed framework is recommended through the triangulation results from pre-test/ post-test, learning environments surveys and students’ written comments, which in turn serves as a guideline for lecturers to identify how they could progressively shift to learner-centred teaching environment.